Thermal performance evaluation of a novel ultra-thin vapor chamber with Laval-like nozzle composite wick under different air cooling conditions. (March 2022) - Zhou, Feng; Zhou, Guohui; Zhou, Jingzhi; Huai, Xiulan; Jiang, Yawen; Huang, Qiang
Abstract: Driven by the continuously increasing cooling demands of electronic devices, ultra-thin vapor chambers (UTVCs) possessing the characteristics of easy-fabrication, low-cost and high-performance are urgently required. In this research, an integrated composite wick with multi-artery channels structure was proposed, which imitates the Laval nozzle in porosity. The designed wick was not only better for liquid reflow and vapor diffusion, but also for supporting the upper and lower covers instead of supporting columns. Under the heat load of 50 W, the UTVC introduced a reduction in maximum temperature difference for 67.7% compared with copper plate with the identical dimensions under natural convection. Under the heat load of 180 W and cooling air flow rate of 72.8 CFM, the UTVC's minimum spreading resistance reaches about 0.063 °C/W. The experimental results and LED's practical applications both indicate that the UTVC enhanced cooling capacity remarkably and yield a notable favorable performance for the heat dissipation of high-power electronic devices.